Is women’s empowerment associated with coverage of RMNCH interventions in low- and middle-income countries? An analysis using a survey-based empowerment indicator, the SWPER - Ewerling, Fernanda (J Glob Health, 2021)
BACKGROUND: Women’s empowerment has a strong potential to promote sustainable development. We evaluate the association between women’s empowerment and the Composite Coverage Index (CCI), a weighted average of coverage of eight interventions in reproductive, maternal, newborn and child health (RMNCH). We also assess whether these effects are modified by wealth. METHODS: We used Demographic and Health Survey data from 62 low- and middle-income countries. Women’s empowerment was measured using the three domains (attitude to violence, social independence and decision making) of the survey-based indicator of women’s empowerment (SWPER). Analyses followed an ecological design. Meta-regression models were used to account for within-country uncertainty in the CCI. We also carried out meta-regression with wealth quintiles of households as the units of analyses and tested for interaction between wealth and each empowerment domain. RESULTS: We found positive associations between the three domains of SWPER and CCI at the country level. One standard deviation change in empowerment increased the CCI by 14.2 percentage points (attitude to violence), 15.3 percentage points (decision-making), and 16.3 percentage points (social independence). The association between social independence and CCI was modified by wealth: each additional standard deviation was associated with 21.8 (95% confidence interval (CI) = 14.0-29.6) and 8.7 (95% CI = 5.4-12.0) percentage points increase in the CCI among the poorest and the richest quintiles, respectively. CONCLUSIONS: Our findings suggest that efforts toward the achievement of SDG5 (Achieve gender equality and empower all women and girls) may support improvements in RMNCH in low- and middle-income countries, especially among the poorest women and children.